PENGARUH MODEL PROBLEM BASED LEARNING ( PBL) TERHADAP HASIL BELAJAR IPA DI KELAS V SEKOLAH DASAR GUGUS III KECEMATAN IV KOTO - fitri, nelsi nadiatul; zen, mulyani; muhammadi, muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to determine the effect of learning with the Model Problem Based Learning (PBL) to the learning outcomes of students in learning science in Grades V Cluster III Elementary School District IV Koto second semester of the academic year 2017/2018. This research was conducted on the material describing the properties of light. This type of research uses quantitative research by using experimental methods, and experimental research design quasy. The research population numbered 121 students and sample by using cluster sampling. The sample was 60 students. According to the research that has been done, then obtained t> t table ie 8.212> 2.001 with α = 0.05, which means that H0 is rejected. The average student learning outcomes as measured by the posttest after learning, that the experimental class 86 and 70. So,  Ha accepted that there are significant learning model using Problem Based Learning (PBL) to the learning outcomes of students in learning science in Class V SD Cluster III Kecamatan IV Koto.